FEATURES OF STRUCTURAL AND FUNCTIONAL DISORDERS OF BONE TISSUE IN CHRONIC HEART FAILURE - Ignatiev, O.M.; Paniuta, O.I.; Prutiian, T.L. (World of Medicine and Biology, 2023)
The purpose of the study was to assess the effect of loop diuretic therapy on the structural and functional condition of bone tissue and phosphorus-calcium metabolism in patients with chronic heart failure and moderately reduced ejection fraction. 109 patients between the ages of 65 and 74 were examined, 86 of them had chronic heart failure, and 23 were practically healthy. The 1st group received basic therapy; the 2nd group – basic therapy and loop diuretics. The examination includes the following: the collection of anamneses, anthropometric measurements, laboratory (determination of natriuretic hormone (B-type), N-terminal polypeptide, C-terminal telopeptide, osteocalcin, osteoprotegerin, 25-hydroxyvitamin D, parathormone, phosphorus) and instrumental (heart ultrasound examination, ultrasound densitometry) investigations. In patients with chronic heart failure, a violation of the processes of bone remodeling with a predominance of bone resorption against the background of slowed bone tissue formation was revealed. In patients with chronic heart failure, structural and functional changes in bone tissue were revealed, which are manifested by an imbalance of bone remodeling processes with a predominance of bone resorption and slowed bone formation, vitamin D deficiency, and significantly low indices of bone mineral density. Moreover, significantly pronounced changes were revealed in the group of patients who were on basic chronic heart failure therapy and loop diuretics comparing with the same indices in patients with chronic heart disease who received only basic therapy.